A Speed-Adaptive Media Encryption Scheme for Real-Time Recording and Playback System. (17th August 2010) - Xiao Xiao, Chen Chen; Lian Lian, Shiguo Shiguo; Wang Wang, Lifeng Lifeng; Ma Ma, Shilong Shilong; Lv Lv, Weifeng Weifeng; Xu Xu, Ke Ke
Abstract : The recording and playback system (RPS) in video conference system needs to store mass of media data real-timely. Considering the security issue, media data should be encrypted before storing. Traditional full encryption and partial encryption algorithms are not applicable to RPS because they could not adjust their speed to meet the throughput variation of media data in real-time RPS. In this paper, a novel lightweight speed-adaptive media-data encryption (SAME) scheme is proposed firstly. Secondly, the SAME is improved to a packet-based algorithm according to the implementation of data storage in RPS system. Thirdly, an RPS oriented queue theory-based autoadaptive speed control mechanism for SAME is designed. Finally, these schemes are integrated into the practical system, that is, AdmireRPS, an RPS of a heterogeneous wireless network-(HWN-) oriented video conference system. Theoretical analysis and experimental results show the SAME is effective enough to support real-time applications. In addition, the proposed schemes also can be used in video surveillance and other video recording systems.